The inside, the outside and the gap in between: Libertarian epistemologies and abolitionist scenic practices (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article is a compilation of three interviews carried out with Latin American artists and researchers: Sayak Valência, Lia Garcia and Maria Galindo. The text organizes the three interviews into a single dramaturgy with the aim of establishing a debate about the intersections present between performing arts, prison abolitionism and gender/sexuality dissent.
Keywords: penal abolitionism; gender; artivism; prision